2016
DOI: 10.1039/c6sm00275g
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetics in polyelectrolyte grafted nanofluidic channels modulated by the ion partitioning effect

Abstract: The effects of ion partitioning on the electrokinetics in a polyelectrolyte grafted nanochannel, which is the representative of a soft nanochannel, are analyzed. Earlier studies in this regard have considered low polyelectrolyte layer (PEL) grafting density at the rigid nanochannel wall and, hence, an equal permittivity inside and outside the grafted layer. In order to overcome this shortcoming, the concept of Born energy is revisited. The coupled system of the modified Poisson-Boltzmann and Navier-Stokes equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 62 publications
0
54
0
Order By: Relevance
“…Accordingly, we do not account for the ion partitioning effect that considers the Born energy difference between PE and electrolyte phase. Chakraborty and coworkers have first considered this effect , although for most of the other studies by the present group and other groups, this effect has been neglected.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Accordingly, we do not account for the ion partitioning effect that considers the Born energy difference between PE and electrolyte phase. Chakraborty and coworkers have first considered this effect , although for most of the other studies by the present group and other groups, this effect has been neglected.…”
Section: Discussionmentioning
confidence: 93%
“…The major weakness of most of the relevant theories stems from the fact that the electric double layer (EDL) electrostatics of the PE brushes is not obtained from the free energy minimization of the entire system that self‐consistently produces the correct brush configuration (i.e., the brush height and the monomer number density); as a consequence, the EDL electrostatics of the PE brush does not reflect the effect of the brush configuration and is based on an erroneous assumption of constant (salt and pH‐independent) brush height and uniform monomer (or equivalently, uniform distribution of the PE chargeable sites or PECS) distribution along the brush . A large number of other transport studies (e.g., liquid transport under different mechanisms) in such brush‐grafted nanochannels have also suffered from such brush‐configuration‐independent description of the PE brush EDL electrostatics .…”
Section: Introductionmentioning
confidence: 99%
“…At interface of the electrolyte and PEL, the potential ( ψ ) and the gradient of the potential (∇ ψ ) satisfies the continuity in potential distribution. Since the relative permittivity of electrolyte and PEL region does not change, we here consider the permittivity of both the PEL and electrolyte to be same 26 . Below we write the boundary conditions as discussed above.…”
Section: Mathematical Modellingmentioning
confidence: 99%
“…Considering all above pertinent issues involved with different bio-medical/biochemical applications, a thorough understanding of the underlying transport of non-Newtonian fluids through a soft narrow fluidic channel appears to be an important aspect for the modifications in the micro-electro-mechanical circuitry, primarily attributed to the complex interplay among different forcings associated with the underlying transport process. Accounting this aspect, a few studies as reported in the literature have delineated the physico-chemical interaction of electromechanics at small scales and fluid dynamics such as charge regulated surface, ion-partitioning effect, higher surface charge (relaxation effect) and surface potential, pH dependent charge density, Field Effect Transistor (FET) regulated surface potential, diffusion effect of ions, specific ion interaction, grafting of end charged polyelectrolyte brushes and their influential impacts on streaming current, streaming potential as well as electro-viscous effect 10 , 13 , 20 26 . But the non-intuitive molecular interactions of the PEL with the apparent viscosity of the non-Newtonian fluid fetches a new framework for fluid flow analysis owing to fit in the shear dependent nature of the fluid viscosity in different applications mentioned above 27 .…”
Section: Introductionmentioning
confidence: 99%
“…A charged solid wall bounding an ionic solution forms an electric double layer at the interface, in which the diffuse ions carry a total charge equal in magnitude but opposite in sign to that of the wall. When an ionic solution filled in a charged narrow channel is subject to an external electric field or pressure gradient that interacts with the double layer, electrokinetic phenomena such as electroosmosis and streaming potential will occur [1][2][3][4][5][6][7][8][9]. Electrokinetic flows are of many fundamental and practical interests in a variety of scientific and technological areas.…”
Section: Introductionmentioning
confidence: 99%